AL-QUR’AN DAN ILMU PENGETAHUAN - Eva Iryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Al-Qur’an is a source of knowledge. This jurnal is made to know the relation between Islam and knowledge, The relation between Al-Qur’an and science, the relation between Al-Qur’an and math, to knowing the expansion between knowledge and Al-Qur’an and, to knowing knowledge and technology. The law of seking knowledge is fardhu ‘ain. (the personal have to do). According to the monitoring, al-qur’an contains all of information that human need. Al-quran as a source of knowledge gives the seeds of knowledge to be expanded by human become a science and technology that very useless. Science correspondency with the  nature accident, so in al-quran more than 750 ayat about the  nature accident. So the conclusion is , Al-Quran and knowledge are the one of unity that can’t be separate.key woard: Al-Qur’an, Islam, Sains, IPTEK